Employee Performance Based on Work Motivation and Work Environment at A Food/Beverage Company - Iriana Kusuma Dewi; Ading Sunarto; Rio Budi Atmaja (Indonesian Journal of Social Research (IJSR), 2022)
The food/beverage business is increasingly popular in cities and suburban areas. This study aims to see the influence of motivation and environmental work on performance employees at the food and beverage company in Cijantung, Jakarta. This study is descriptive quantitative with taking a sample of 75 employees. This study uses primary data, namely data, in a distributed questionnaire to the respondent for filling in. The data obtained were analyzed using test validity, reliability, classic test assumption, analysis regression, coefficient correlation, coefficient analysis determination, and hypothesis testing. Research results show that motivation and environmental work are significant to performance employees. Because if problem security in position, as well no existence more rewards during the pandemic and opportunity promotion low employee make desire or Motivation employee in work will be reduced. Likewise, if the conditioned room, ventilation, and lighting illuminator are not in the proper position, employees will not be comfortable in work, which could lower performance. Because of that, food and beverage companies must do inspection comprehensive covering procedures and policies company for increasing passion and passion employees.